The cocoa value chain in Ucayali: Analysis to identify business models with agroecological potential - Charry, Andres; Torres, Nelson; Fonseca, Cristina; Narjes, Manuel (2023)
This report provides an update on the state of the art of the cocoa value chain in Ucayali, along with a discussion on its existing business models and their associated challenges and opportunities. This analysis is conducted within the framework of the 13 agroecological principles outlined by the High Level Panel of Experts (HLPE, 2019). Our analysis is based on a review of secondary information, interviews with indirect actors across the value chain in the region, and information provided by representatives of producer organizations in the area, each employing different strategies for their development.